2021
DOI: 10.3758/s13421-021-01186-x
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of source claims on statement believability and speaker accountability

Abstract: What is the effect of source claims (such as "I saw it" or "Somebody told me") on the believability of statements and what mechanisms are responsible for this effect? In this study, we tested the idea that source claims impact statement believability by modulating the extent to which a speaker is perceived to be committed to (and thereby accountable for) the truth of her assertion. Across three experiments we presented participants with statements associated with different source claims, asked them to judge ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…While the correct conceptual analysis of “memory” is debated in philosophy (e.g., Michaelian & Robins, 2018), hardly anyone denies that we have different concepts for memory and imagination. Finally, claims to remembering and imagining have starkly different social consequences and are applied in different contexts (Mahr & Csibra, 2020; 2021; Mahr, Mascaro, Mercier, & Csibra, 2021). In sum, remembering and imagining seem to be distinguished as a matter of phenomenology, as a matter of concepts, and as a matter of social practice.…”
Section: Mnemicity As Cognitive Attributionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the correct conceptual analysis of “memory” is debated in philosophy (e.g., Michaelian & Robins, 2018), hardly anyone denies that we have different concepts for memory and imagination. Finally, claims to remembering and imagining have starkly different social consequences and are applied in different contexts (Mahr & Csibra, 2020; 2021; Mahr, Mascaro, Mercier, & Csibra, 2021). In sum, remembering and imagining seem to be distinguished as a matter of phenomenology, as a matter of concepts, and as a matter of social practice.…”
Section: Mnemicity As Cognitive Attributionmentioning
confidence: 99%
“…This makes sense because when someone disagrees with us it pays to make sure that we have good reasons for holding the belief in question—this allows us both to evaluate whether to update that belief and to produce reasons for our interlocutor to accept it. Moreover, having formed a belief based on personal experience should be particularly effective in convincing others: such experience does not just have special epistemic status in its own right but also claims to first‐hand knowledge also more strongly commit the speakers to the truth of their assertion serving as a signal of reliability (Mahr & Csibra, 2021).…”
Section: Individual Aspects Of Mnemicity Attributionmentioning
confidence: 99%
“…1 In this sense, memory owes its epistemic reliability to the hyper-veridical status that we attribute to perception. Such an intuitive notion of memory explains why claims made on the basis of first-hand evidence (i.e., testimony) ceteris paribus seem to be taken to have higher epistemic reliability than beliefs formed on the basis of other sources (Mahr & Csibra, 2021). However, in contrast to this intuitive characterization of remembering, research on episodic memory has consistently found that remembering is a constructive, highly inferential and malleable process (Bartlett, 1932;Schacter & Addis, 2007).…”
Section: Intuitive Theories Might Serve Coordinative Social Functionsmentioning
confidence: 99%
“…How can we make sense of the contradiction between the intuitive epistemic immediacy and empirical constructiveness of remembering? Elsewhere, we have proposed that what makes a testimony appear more reliable than other types of information is not its epistemic validity but the very fact that the speaker is willing to take responsibility for its content (Mahr & Csibra, 2018, 2021. Coordinating beliefs about what happened in the past plays a particularly central role in human social life: most of our social commitments, entitlements, and obligations are ultimately only justifiable through reference to past events (Mahr & Csibra, 2020).…”
Section: Intuitive Theories Might Serve Coordinative Social Functionsmentioning
confidence: 99%
“…For instance, the speaker's confidence in expressing a message impacts both on the message's credibilityby increasing its chances of being accepted by the interlocutorand the speaker's accountabilitynamely the social repercussions if the message is found to be unreliable (Vullioud et al, 2017;Mazzarella, Reinecke, Noveck, & Mercier, 2018). Similarly, evidential claims have been shown to have an impact on the message's credibility as well as the speaker's accountability (Mahr & Csibra, 2021).…”
Section: Introductionmentioning
confidence: 99%